South African endomyocardiopathy and cardiomyopathies in certain laboratory animals : a comparative morphological study - Van der Walt, Johannes Joachim (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.D.) -- University of Stellenbosch, 1974.